A Benchmark Quantum Yield for Water Photoreduction on Amorphous Carbon Nitride. (14th August 2017) - Rahman, Mohammad Z.; Tapping, Patrick C.; Kee, Tak W.; Smernik, Ronald; Spooner, Nigel; Moffatt, Jillian; Tang, Youhong; Davey, Kenneth; Qiao, Shi‐Zhang
Abstract: Amorphous carbon nitride (a‐CN) is a less‐explored but promising photocatalyst for hydrogen production. Despite an extended visible light absorption (EVLA) its low quantum efficiency (QE) for water photoreduction is a long standing problem. This implies that EVLA is not proportionally translated into collection of large amounts of photogenerated electrons. Minimizing the mismatch between light‐absorption and charge‐collection remains a scientific challenge. Here a sponge‐like hierarchical structure of a‐CN that addresses this apparent mismatch is reported. Combined experimental and finite difference time domain simulations demonstrate the ability of the a‐CN sponge to induce scattering for total internal light reflection that promotes localized charge carrier generation. Diffused reflectance and transient fluorescence decay studies show good agreement with simulations with a 40% enhanced light‐trapping and an ≈23 times longer electron lifetime in spongy a‐CN compared with that of the bulk material. The result is a new high benchmark for hydrogen production of 203.5 µmol h −1 with a QE of 6.1% at 420 nm in a reaction system of 10 vol% triethanolamine and 1 wt% Pt cocatalyst. The enhanced water photoreduction is a result of amenable photophysical and electrochemical attributes existing within the a‐CN sponge. Abstract : Spongy amorphous carbon nitride (a‐CN) has been developed and demonstrated for photocatalytic hydrogen production via water‐splitting. Hydrogen production with a‐CN has an apparent quantum efficiency of 6.1% under visible light irradiation (420 nm). This is a high benchmark for hydrogen production, superseding all previously reported a‐CN photocatalysts.